Subclinical Left Ventricular Dysfunction Detected by Speckle-Tracking Echocardiography in Breast Cancer Patients Treated With Radiation Therapy: A Six-Month Follow-Up Analysis (MEDIRAD EARLY‐HEART study) - Locquet, Médéa; Spoor, Daan; Crijns, Anne; van der Harst, Pim; Eraso, Arantxa; Guedea, Ferran; Fiuza, Manuela; Santos, Susana Constantino Rosa; Combs, Stephanie; Borm, Kai; Mousseaux, Elie; Gencer, Umit; et al. (Frontiers in Oncology, 2022)
Background In the case of breast cancer (BC), radiotherapy (RT) helps reduce locoregional recurrence and BC-related deaths but can lead to cardiotoxicity, resulting in an increased risk of long-term major cardiovascular events. It is therefore of primary importance to early detect subclinical left ventricular (LV) dysfunction in BC patients after RT and to determine the dose–response relationships between cardiac doses and these events. Methods Within the frame of the MEDIRAD European project (2017–2022), the prospective multicenter EARLY‐HEART study (ClinicalTrials.gov Identifier: NCT03297346) included chemotherapy naïve BC women aged 40–75 years and treated with lumpectomy and adjuvant RT. Myocardial strain analysis was provided using speckle‐tracking echocardiography performed at baseline and 6 months following RT. A global longitudinal strain (GLS) reduction >15% between baseline and follow-up was defined as a GLS-based subclinical LV dysfunction. Individual patient dose distributions were obtained using multi-atlas-based auto-segmentation of the heart. Dose-volume parameters were studied for the whole heart (WH) and left ventricle (LV). Results The sample included 186 BC women (57.5 ± 7.9 years, 64% left-sided BC). GLS-based subclinical LV dysfunction was observed in 22 patients (14.4%). These patients had significantly higher cardiac exposure regarding WH and LV doses compared to patients without LV dysfunction (for mean WH dose: 2.66 ± 1.75 Gy versus 1.64 ± 0.96 Gy, p = 0.01). A significantly increased risk of subclinical LV dysfunction was observed with the increase in the dose received to the WH [ORs from 1.13 (V5) to 1.74 (Dmean); p <0.01] and to the LV [ORs from 1.10 (V5) to 1.46 (Dmean); p <0.01]. Based on ROC analysis, the LV-V5 parameter may be the best predictor of the short-term onset of subclinical LV dysfunction. Conclusion These results highlighted that all cardiac doses were strongly associated with the occurrence of subclinical LV dysfunction arising 6 months after BC RT. Whether measurements of GLS at baseline and 6 months after RT combined with cardiac doses can early predict efficiently subclinical events occurring 24 months after RT remains to be investigated.